Placenta Previa; Risks and Morbidity (Medical Forum Monthly, 2024)
Objective: To evaluate and determine the risk factors and outcome of placenta previa in patients undergoing cesarean section at Islam Teaching Hospital. Sialkot.Study Design: Case control, Observational and comparative studyPlace and Duration of Study: This study was carried out at the Department of Obstetrics and Gynaecology, Islam Teaching Hospital, Islam Medical College, Sialkot from September 2010 to December 2014.Materials and Methods: Our study included all the patients who underwent caesarean section for singleton pregnancy after 28 weeks of gestation during the study period, data was collected and analyzed retrospectively for determining risk factors and patients were followed prospectively to see the morbidity and outcome of cesarean section in patients with placenta previa labeled as Group I and patients without placenta previa labeled as Group II. The patients who had normal vaginal delivery were not included in the study. Data was recorded using SPSS version 20 and frequencies were calculated. Statistical analysis and significance was done using OpenEpi calculators. P value was calculated using two by two table and relevant Fischer and mid-P extract tests. P value <0.05 was used to show significant difference.Results: During the specified period 46 patients were those whose pregnancy was complicated by placenta previa while 734 patients who underwent cesarean section were not having antenatal or peroperative evidence of placenta previa. The maternal age >35years was present in 27 patients in group 1 and 234 patients in group11 so placenta previa is associated with age greater than 35 years (OR 3.036, 95%CI 1.655-5.572, P value 0.0001700)The multivariate retrospective analysis showed that independent factors of prior LSCS (OR 2.33, 95% CI 1.272-4.271, P value 0.003940) previous history of D&C (OR 2.341, 95% CI 1.029 -4.936, P value 0.02163 ) and malpresentation (OR 4.142, 95% CI 1.852-8.725, P value 0.0005307) were associated with placenta previa.Placenta previa was associated with adverse maternal outcome. In our study postpartum haemorrhage occurred in 20 patients of group I as compared to group II (43.47% vs 5.3%, P value <0.05 ). But massive blood transfusion (transfusion of more than 4 units of blood ) was required in 8 patients in group 1 as compared to 22 patients in group II (17.4% vs 3.0%, P value <0.05). Cesarean Hysterectomy was done in 4 patients in group I and no caesarean hysterectomy was required in group II (8.6% vs 0.00%, P value <0.005). In 3 patients, indication of hysterectomy was placenta accreta with previous history of cesarean section. In one patient there was fibroid uterus along with placenta previa; so fibroid uterus was a confounding factor in our study so that cesarean hysterectomy percentage is somewhat more in our study. In all 3 cases of placenta accreta, there was history of previous cesarean section so that there is 15% chance of placenta accreta in patients with previous history cesarean section along with placenta previa. The placenta previa was also associated with adverse fetal outcome as perinatal mortality (17.4% vs 2.9%, P value <0.05), low APGAR score at 5 min (19.6% vs 7.1%, P value <0.05) congenital anomalies (10.8% vs 4.1%, P value <0.05 ) was high in group I patients. Placenta previa was not associated with intrauterine growth restriction (4.3%vs 2.6%, P value 0.2379).Conclusions: Advanced maternal age, previous caesarean section, previous history of D&C and malpresentation are associated with increased risk of placenta previa. Placenta previa is definitely associated with adverse maternal as well as neonatal outcomes. The obstetrician should be vigilant in antenatal as well as peripartum care of such patients in order to manage the associated complications and to decrease maternal and fetal morbidity and mortality.